2019
DOI: 10.1111/apha.13376
|View full text |Cite
|
Sign up to set email alerts
|

Principal mode of Syndecan‐4 mechanotransduction for the endothelial glycocalyx is a scissor‐like dimer motion

Abstract: Aim Endothelial glycocalyx (EG) plays a pivotal role in a plethora of diseases, like cardiovascular and renal diseases. One hallmark function of the EG as a mechanotransducer which transmits mechanical signals into cytoplasm has been documented for decades. However, the basic question ‐ how the glycocalyx transmits the flow shear stress— is unanswered so far. Our aim is to shed light on the fundamental mode of signal transmission from flow to the endothelial cytoskeleton. Methods We conduct a series of large‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…However, they are able to form α-helices in presence of trifluoroethanol. This is in agreement with the partial folding into α-helix of the ectodomain of syndecan-4 during molecular dynamic simulations carried out at the glycocalyx level [47] .…”
Section: Discussionsupporting
confidence: 87%
“…However, they are able to form α-helices in presence of trifluoroethanol. This is in agreement with the partial folding into α-helix of the ectodomain of syndecan-4 during molecular dynamic simulations carried out at the glycocalyx level [47] .…”
Section: Discussionsupporting
confidence: 87%
“…In conclusion, in accordance with previous studies are the calculations by Jiang et al of the uncovered transmitted force in the order of 10‐100pN and the presence of a threshold in GAG reduction and changes in mechanotransduction. Together with earlier calculations this could mean that syndecan‐4 transduces force only at a certain threshold of shear stress to which endothelial cells will respond.…”
supporting
confidence: 92%
“…According to the same published model, assuming the endothelial glycocalyx as a rigid body in which the torque of the whole layer was studied, cytoskeletal deformation would be inhibited only when all sugar chains of the glycocalyx were removed, although other experiments suggest a threshold in which about 30%‐45% reduction already would inhibit cytoskeletal reorganization. Reconciling these differences, the soft matter model proposed in this study shows that flexibility of the linkage between the ecto‐ and transmembrane subdomains of the core protein allows that forces can only partly be transmitted into the cytoskeleton. Thus by only removing 16.7% of the sugar chains, in terms of scissors angular variation, result already in a reduction of 55% in mechanotransduction.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In the classic vasoregulation signalling problem -in what manner does glycocalyx transmit force to the cytoskeleton from the flowing blood?, the glycocalyx was regarded as a rigid body and the force was transmitted by the local torque induced by the movement of the glycocalyx core protein. In recent MD simulations, Jiang et al (2020b) elucidated the dynamics of Syndecan-4 (a typical type of transmembrane protein of the glycocalyx), and concluded that a scissor-like motion of the Syndecan-4 transmembrane dimer, together with its bending, is responsible for the force transmission and the force transmitted into the cytoplasm is of an order 10-100 pN. The MD model and force transmission mode is summarised in Figure 2.…”
Section: Microscopic Simulationsmentioning
confidence: 99%